Cost and policy determinants of features of tractor markets in Nigeria: Case studies of tractor sellers in Kaduna state and tractor owners in Benue state - Hatzenbuehler, Patrick L.; Takeshima, Hiroyuki; Edeh, Hyacinth O.; Lawal, Akeem (International Food Policy Research Institute, 2018)
In this study, we contribute to such efforts to enhance the use of tractors in Africa by describing the key characteristics of markets for tractors in Nigeria. Nigeria is among a set of countries in Africa that has both low agricultural productivity and low agricultural mechanization growth (Malabo Montpellier Panel 2018). Current understanding of the tractor market in Nigeria mainly highlights only specific aspects of mechanization issues or only delves into the application of specific emergent mechanization technologies. Consequently, many stakeholders do not have sufficient understanding of how tractor markets in Nigeria are organized both in vertical and in geographic terms.